2007
DOI: 10.1042/bj20061808
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-, concentration- and cholesterol-dependent translocation of L- and D-octa-arginine across the plasma and nuclear membrane of CD34+ leukaemia cells

Abstract: Delineating the mechanisms by which cell-penetrating peptides, such as HIV-Tat peptide, oligoarginines and penetratin, gain access to cells has recently received intense scrutiny. Heightened interest in these entities stems from their ability to enhance cellular delivery of associated macromolecules, such as genes and proteins, suggesting that they may have widespread applications as drug-delivery vectors. Proposed uptake mechanisms include energy-independent plasma membrane translocation and energy-dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
222
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(240 citation statements)
references
References 34 publications
14
222
3
Order By: Relevance
“…The diffuse staining was not due to the release of peptide from endosomes as it appeared first and the punctate staining later, and it continued to occur at 4°C when endocytosis is inhibited. Several other studies have also reported cellular uptake when the cells have been incubated at 4°C [26,[51][52][53]. It has also been observed that blocking specific endocytotic pathways does not affect the ability of TAT peptide to enter cells.…”
Section: Direct Translocation Endocytosis: An Either/or Discourse?mentioning
confidence: 91%
See 1 more Smart Citation
“…The diffuse staining was not due to the release of peptide from endosomes as it appeared first and the punctate staining later, and it continued to occur at 4°C when endocytosis is inhibited. Several other studies have also reported cellular uptake when the cells have been incubated at 4°C [26,[51][52][53]. It has also been observed that blocking specific endocytotic pathways does not affect the ability of TAT peptide to enter cells.…”
Section: Direct Translocation Endocytosis: An Either/or Discourse?mentioning
confidence: 91%
“…The TAT protein is an 86 amino acid long protein that is released by infected cells and is an essential regulatory gene for HIV replication [8]. In 1997, Vives et al [9] found that a 11-amino acid sequence, TAT (47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57), now known as the TAT peptide or TAT PTD, can not only enter cells but is more efficient than the full length protein. It was observed that the chirality of the peptide backbone has no effect on cellular uptake of TAT peptide; inverse and retro forms were able to enter cells as efficiently as the native peptide, suggesting uptake does not require a specific binding site.…”
Section: Tat As a Prototypical Example Of A Cell-penetrating Peptidementioning
confidence: 99%
“…Internalization has consequently been suggested to occur via different routes of endocytosis, potentially including macropinocytosis, clathrin-and caveolin mediated endocytosis, as well as via a mode of entry by direct membrane penetration at high peptide concentrations. 125,[133][134][135] Although direct membrane penetration was proposed as a potential route of entry for PTDs alone, uptake of arginine-rich PTDs linked to macromolecular cargoes appears to occur solely by endocytosis. 127,134,136 Since routes of entry appear to be similar for most PTDs and delivery efficiency is subject to the same limitations, the potential applications of well-characterized PTDs are worth considering, rather than searching for the "best PTD."…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…The translocation can take place via the energy dependent or independent route and multiple factors have been suggested to control the balance between various internalization pathways [14][15][16]. Similarly, some reports suggest direct translocation to the cell of TP10 [17,18], whereas other studies suggest its endocytosis [12,19]. Thus, we aimed to check possible method of TP and TP10 penetration into CRC cells by determining their transport ratios after inhibition of endocytosis with the use of brefeldin A [20][21][22].…”
Section: Introductionmentioning
confidence: 99%